1. Penela, D., Cardoso, M. G. M. S., Gregory, A. (2023). Recognizing cognitive, affective, and sensory aspects in accommodation choice for families of children with ASD and ADHD. - Penela, D.; Cardoso, M. G. M. S.; Amy M. Gregory (7th World Research Summit for Hospitality and Tourism., 2023)
Families of children with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) are known to have special needs as it relates to the environments in which they live, work, and play. This study intends to analyze which attributes of lodging accommodations these families are most likely to prioritize and uncover segments that may reveal different priorities in accommodation choice. Building on extant literature that suggests that consumers, in general, consider cognitive, affective, and sensory attributes together during accommodation choice, this study investigates the considerations of the growing population of families of children with ADHD/ASD by applying and amending current research models. Cognitive attributes refer to aspects such as price, service, food quality, recognized brand, and recreational facilities; affective attributes refer to comfort, and entertainment (including feelings such as excitement, pampered, and interest); and sensory attributes include room quality (encompassing cleanliness, quietness, and the comfort of furnishings) and overall atmosphere (such as music and the overall hotel environment). Segmentation based on 526 qualified families, resorting to a finite mixture model, uncovers three segments that exhibit different rankings of the attributes considered when choosing an accommodation. A binary indicator distinguishing between families with a child who has been formally diagnosed and those with a child suspected of having ASD/ADHD/sensory processing impairment is also used as a covariate. As an interesting and unique contribution to the fields of hospitality and psychology, results show a larger segment (41%) of families that have a majority of formally diagnosed cases and tend to value more “Accommodations for my family's specific needs”, “Staff awareness/training for ASD/ADHD Accommodations”, “Noise level/quietness”, and “Privacy”. The smallest segment (23.2%) has a majority of non-diagnosed cases and is one that values the least the referred attributes. The remaining segment clearly shows very high price sensitivity although its general profile does not differ much from the first/largest segment.